Pengabdian kepada Masyarakat berupa Pendidikan Kesehatan Terkait Infeksi Saluran Pernapasan Akut (ISPA) : Pendidikan Kesehatan Infeksi Saluran Pernapasan Akut (ISPA) kepada Masyarakat Pengunjung Puskesmas Kecamatan Cinere, Depok, Jawa Barat - Suratmini, Dwi; Jansen, Susiana; Ardhiyanti, Lusyta Puri (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2023)
Acute Respiratory Infections (ARI’s) is the most infectious disease in the world. ARI’s often attacks children, where ARI’s occupies the top 10 diseases that infect children. In Indonesia, ARI’s still requires special handling. Counseling inthe form of health education related to ARI’s in the community is expected to be able to increase public knowledge regarding ARI’s and influence public attitudes in preventing ARI’s. The results of community service activities at The Cinere Public Health Center, Depok City West Java are increasing knowledge and understanding of the community regarding ARI’s starting from the definition, causes, classification, signs and symptoms, risk factors and prevention ofARI’s.   Keywords: ARI’s; education; health; knowledge